Evaluation of serum uric acid in acute ischaemic stroke - Kaur, Inderjeet; Khurana, Ashok; Sachdev, Jasmine Kaur; Mohan, Gurinder (International Journal of Advances in Medicine, 2017)
Background: The role of serum uric acid as a risk factor for acute ischaemic stroke is controversial and there is little information about it. Present study was done to estimate serum uric acid levels in patients of acute ischaemic stroke and to assess its risk factor potential. Methods: It was a prospective case control study carried out in the department of Medicine at Sri Guru Ramdas Institute of Medical Sciences and Research, Vallah, Sri Amritsar, Punjab, India from January 2015 to July 2016. 50 cases of acute ischaemic stroke were enrolled and were compared with same number of age and sex matched healthy controls. Serum uric acid levels were measured in cases (within 24 hours of stroke evolution). Glasgow coma scale (GCS) score was calculated for cases at time of admission. The results were statistically analysed. Results: Mean serum uric acid level in cases was 6.15±1.91mg/dl whereas it was 5.1±1.4 mg/dl in controls. The difference of serum uric acid levels between cases and controls was statistically significant (p = 0.0054). Patients with poor GCS had higher mean serum uric acid levels as compared to patients with mild or moderate GCS score which was statistically significant(p = 0.0426). Conclusions: Serum uric acid can be used as a marker for increased risk of stroke. Furthermore, serum uric acid can also be used for risk stratification after stroke.